Effect of polyurethane/nanosilica composite coating on thermomechanical properties of polyethylene film - Ching, Y C; Ching, Y C; Yaacob, Iskandar Idris (Maney Publishing, 2012)
Polyurethane (PU)/nanosilica composite was fabricated and then coated on polyethylene (PE) film using a rod Mayer technique. The silica nanoparticles used have an average particle size of 16 nm, and their weight fractions varied from 0 to 14%. Two different thicknesses of PU/nanosilica coating layer were fabricated, which were 4 and 8 μm. The morphology and thermal mechanical properties of the nanocomposite coated PE film were characterised using scanning electron microscope, dynamic mechanical analyser, thermogravimetric analyser as well as tensile tests. The results showed that a thin layer coating of PU/nanosilica composite has a slightly reduced tensile strength of the PE substrate. However, the nanocomposite coating of up to 8 μm reduced the elongation of PE substrate significantly. The PU/nanosilica composite coating layer increased the tensile modulus and stiffness of the PE substrate. There was no influence of PU/nanosilica composite coating on the thermal degradation rate of the PE film.